Possible association of diazotrophs with marine zooplankton in the Pacific Ocean. Issue 6 (28th June 2016) - Azimuddin, Kazi Md.; Hirai, Junya; Suzuki, Shotaro; Haider, Md. Nurul; Tachibana, Aiko; Watanabe, Keigo; Kitamura, Minoru; Hashihama, Fuminori; Takahashi, Kazutaka; Hamasaki, Koji
Abstract : To understand the diversity and abundance of putative diazotrophic communities associated with marine zooplankton, especially copepods, the molecular diversity of the nifH gene was studied by nested PCR amplification, followed by cloning and sequencing of zooplankton‐associated microorganisms DNA collected from the Pacific Ocean. Abstract: Dinitrogen fixation, the biological reduction in N2 gas to ammonia contributes to the supply of new nitrogen in the surface ocean. To understand the diversity and abundance of potentially diazotrophic (N2 fixing) microorganisms associated with marine zooplankton, especially copepods, the nifH gene was studied using zooplankton samples collected in the Pacific Ocean. In total, 257 nifH sequences were recovered from 23 nifH ‐positive DNA extracts out of 90 copepod samples. The nifH genes derived from cyanobacteria related to Trichodesmium, α ‐ and γ ‐subdivisions of proteobacteria, and anaerobic euryarchaeota related to Methanosaeta concilii were detected. Our results indicated that Pleuromamma, Pontella, and Euchaeta were the major copepod genera hosting dinitrogen fixers, though we found no species‐specific association between copepods and dinitrogen fixers. Also, the digital PCR provided novel data on the number of copies of the nifH gene in individual copepods, which we report the range from 30 to 1666 copies per copepod. This study is the first systematic study of zooplankton‐associated diazotrophs, covering a large area of the open ocean, which provide a clue to further study of a possible new hotspot of N2 fixation.